The political construction of sport in the Peruvian educational system: a look at the contents of the Physical Education course during the 20th century - Marceillac, Mariana (2020)
The Physical Education contents in the national curriculum express political projects and changing ideas about what we want sport to be for new generations over time. This research identifies the socio-political utility given by the Peruvian State to Physical Education throughout the 20th cen-tury, distinguishing three different visions of sport for society. The course was inserted in schools at the beginning of the century to solve social problems: strengthening the race, fighting bad habits, and achieving national industrialization and modernization. Between 1950 and 1979, it was closely related to Premilitary Education and the generation of patriotism. Since 1980, the reconceptualiza-tion of the course based on individual development and not on socio-political interests left Physical Education and sport at the end of the queue compared to other State priorities. Efforts to develop Peruvian sport have been reinitiated, but their success depends on defining a clear national vision and project, as well as taking action from schools.